The people we hate at the wedding [large type] - Ginder, Grant (Thorndike Press, a part of Gale, a Cengage Company, 2017)
"Relationships are awful. They'll kill you, right up to the point where they start saving your life. Paul and Alice's half-sister Eloise is getting married! In London! There will be fancy hotels, dinners at "it" restaurants and a reception at a country estate complete with tea lights and embroidered cloth napkins. They couldn't hate it more. The People We Hate at the Wedding is the story of a less than perfect family. Donna, the clan's mother, is now a widow living in the Chicago suburbs with a penchant for the occasional joint and more than one glass of wine with her best friend while watching House Hunters International. Alice is in her thirties, single, smart, beautiful, stuck in a dead-end job where she is mired in a rather predictable, though enjoyable, affair with her married boss. Her brother Paul lives in Philadelphia with his older, handsomer, tenured track professor boyfriend who's recently been saying things like "monogamy is an oppressive heteronormative construct," while eyeing undergrads. And then there's Eloise. Perfect, gorgeous, cultured Eloise. The product of Donna's first marriage to a dashing Frenchman, Eloise has spent her school years at the best private boarding schools, her winter holidays in St. John and a post-college life cushioned by a fat, endless trust fund. To top it off, she's infuriatingly kind and decent. As this estranged clan gathers together, and Eloise's walk down the aisle approaches, Grant Ginder brings to vivid, hilarious life the power of family, and the complicated ways we hate the ones we love the most in the most bitingly funny, slyly witty and surprisingly tender novel you'll read this year"--